Closing Tobacco Treatment Gaps for Rural Populations: The Role of Clinic-Based Pharmacists at a Federally Qualified Health Center - Lavinia Salama; Karen Suchanek Hudmon; Leena Myran; Nervana Elkhadragy (Pharmacy)
Pharmacists are often the first point of contact for healthcare advice in rural communities, where access to healthcare is limited. Tobacco cessation rates improve with counseling from a pharmacist, and in many states, pharmacists can now prescribe medications for quitting. This study aimed to explore smoking behavior and cessation motivations among patients at a Federally Qualified Health Center (FQHC) clinic in rural Wyoming, estimate the prevalence of tobacco-related interventions by clinic staff, and assess patients’ interest in engaging in pharmacist-led cessation programs. A cross-sectional survey was administered over three months to clinic patients who self-identified as current tobacco users. Survey items assessed sociodemographics, tobacco use and vaping behaviors, previous cessation advice from pharmacists, and interest in pharmacist-led support for quitting. Of 63 respondents, 57 (90.5%) reported current tobacco use. Most were ready to quit within the next month (43.9%) or the next six months (33.3%), and 26.3% had previously received advice about quitting from a pharmacist. Most (59.6%) expressed interest in establishing care with a pharmacist for cessation support, and 45.3% requested to be contacted by a pharmacist for assistance with quitting. Interest did not differ by gender or age. The results indicate that rural patients are interested in engaging with pharmacists for quitting. Further research is needed to determine how pharmacy-led programs can complement existing healthcare resources to improve access to cessation support in underserved areas.